Insulating and heat conductive sheet
Patent Information
- Application Number
- JP2022085096
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-05-25
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2042-05-25
AI Technical Summary
【0013】 本発明の絶縁性熱伝導シートは、厚さ方向の熱伝導性に優れ、電気絶縁性にも優れていながら、低硬度で柔軟性に優れる。
Smart Images

Figure 0007630895000011 
Figure 0007630895000012 
Figure 0007630895000013
Abstract
Description
[Technical field]
[0001] The present invention relates to a thermally conductive sheet having electrical insulation properties. [Background technology]
[0002] In recent years, as electronic devices become more sophisticated, the density and packaging of semiconductor elements are becoming higher. As a result, the amount of heat generated by the electronic components that make up electronic devices is also increasing, making it important to dissipate heat efficiently. In response to this, heat sinks and other heat dissipators are generally used to dissipate the heat generated by heat generating bodies. It is known that a heat dissipation sheet is placed between the heat generating body and the heat dissipating body to improve the heat transfer efficiency.
[0003] In particular, the electronics of automobiles has become increasingly sophisticated, and the number of electronic components mounted on them has increased, leading to an increased demand for heat dissipation materials. Heat dissipation materials come in sheet and grease types, but the sheet type is often preferred due to its ease of mounting. Furthermore, in the context of autonomous driving, there is a demand for further improvement in the thermal conductivity of such heat dissipation materials. Generally, in order to achieve high thermal conductivity, it is necessary to increase the filling rate of the filler dispersed within the polymer, which tends to increase the specific gravity, but this is a problem in promoting weight reduction to improve the fuel efficiency of gasoline-powered vehicles and the electricity consumption of electric vehicles.
[0004] For example, Patent Document 1 proposes a method for producing a thermally conductive resin sheet, which includes at least a curing step of extruding a thermally conductive composition containing a polymer, an anisotropic filler, and a packing agent using an extruder, and curing the extrusion to obtain a cured product, and a cutting step of cutting the cured product to a predetermined thickness using an ultrasonic cutter in a direction perpendicular to the extrusion direction.
[0005] Also, for example, Patent Document 2 proposes a method for manufacturing a thermally conductive sheet, in which a magnetic field is applied to a thermally conductive composition containing a polymer, an anisotropic filler, and a bulking agent to orient the anisotropic thermally conductive filler, form a bulk compact, and slice the bulk compact to the desired sheet thickness.
[0006] Also, for example, Patent Document 3 proposes a method for producing a thermally conductive sheet, in which a thermally conductive composition containing a polymer, an anisotropic filler, and a packing agent is rolled, pressed, extruded, or coated to a thickness of 20 times or less the average major axis of the anisotropic filler to produce an oriented primary sheet, and then a molded body obtained by laminating the primary sheets is sliced.
[0007] Furthermore, Patent Document 4 also proposes a method for manufacturing an insulating and thermally conductive sheet in which a primary sheet is produced in which flat boron nitride is highly filled and oriented in aramid resin, and then an insulating adhesive layer is applied to the primary sheet, and the laminated molded body is sliced.
[0008] However, the thermally conductive sheets obtained by these conventional methods tend to have high hardness due to the high filling and orientation of anisotropic fillers such as boron nitride, which reduces adhesion to heat-generating components and makes it difficult to achieve sufficient heat dissipation. In addition, thermal conductive sheets generally expand and contract as the heat-generating components heat up and down, which raises serious concerns about long-term reliability when the laminated interface is made of different materials or has different hardness. [Prior art documents] [Patent documents]
[0009] [Patent Document 1] JP 2012-023335 A [Patent Document 2] JP 2019-186555 A [Patent Document 3] JP 2017-126614 A [Patent Document 4] International Publication No. 2021 / 090929 Summary of the Invention [Problem to be solved by the invention]
[0010] SUMMARY OF THE PRESENT EMBODIMENTS Accordingly, an object of the present invention is to provide an insulating heat conductive sheet which is excellent in thermal conductivity in the thickness direction and is flexible. [Means for solving the problem]
[0011] As a result of intensive research to solve the above problems, the inventors discovered that by highly orienting boron nitride and controlling the crosslinking structure of silicone resin, it is possible to obtain an insulating heat conductive sheet that is flexible and has excellent thermal conductivity in the thickness direction, and thus completed the present invention. That is, the present invention provides the following insulating thermally conductive sheet.
[0012] [1] The following components (A) and (B): (A) a thermosetting silicone resin containing the following (A1) to (A3): 100 parts by mass (A1) Organopolysiloxane having two or more alkenyl groups bonded to silicon atoms in each molecule (A2) an organohydrogenpolysiloxane consisting of the following (A2-a) and (A2-b): an amount such that the molar ratio of the total number of hydrosilyl groups in the component (A2) to the alkenyl groups bonded to silicon atoms in the component (A1) is 0.7 to 1.0: (A2-a) Organohydropolysiloxane represented by the following formula (a): [ka] (m is 2 or 3, n is a number from 10 to 50, and the bonding order of each siloxane unit bounded by m and n may be block or random.) (A2-b) Organohydropolysiloxane represented by the following formula (b): [ka] (p is a number between 10 and 30) (The molar ratio of the above component (A2-a) to component (A2-b) is component (A2-a):component (A2-b)=1:0.2 to 1:2.) (A3) Hydrosilylation catalyst: an amount equivalent to 100 to 3,000 ppm in terms of platinum group metal atoms per 100 parts by mass of component (A1) (B) Boron nitride having an average particle size of 40 to 100 μm and an aspect ratio of 20 to 100 as measured by a laser diffraction / scattering method: 150 to 500 parts by mass An insulating and thermally conductive sheet which is a cured product of a thermally conductive silicone resin composition comprising: The insulating thermally conductive sheet has a degree of orientation in the thickness direction detected by X-ray diffraction method, the sum of counts at [2θ=41 to 43°] / the sum of counts at [2θ=25 to 27°] being 1 or more. [2] The insulating and thermally conductive sheet according to [1], having an Asker C hardness of 20 to 60. [3] The insulating thermally conductive sheet according to [1] or [2], having a thermal conductivity in the thickness direction of 16 to 30 W / mK. [4] The insulating thermally conductive sheet according to any one of [1] to [3], which has a dielectric breakdown voltage of 5 kV / mm or more. [5] The insulating and thermally conductive sheet according to any one of [1] to [4], which has a specific gravity of 1.2 to 2.0. Effect of the Invention
[0013] The insulating thermally conductive sheet of the present invention has excellent thermal conductivity in the thickness direction and excellent electrical insulation, while also having low hardness and excellent flexibility. [Brief description of the drawings]
[0014] [Figure 1] FIG. 2 is a perspective view showing an example of a mold used in a filling step. [Diagram 2] FIG. 2 is a cross-sectional view showing a cross-sectional structure of the mold shown in FIG. [Diagram 3] FIG. 2 is an exploded perspective view showing an example of a mold used in a molding process. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] The present invention will be described in detail below, but the present invention is not limited thereto. [Insulating heat conductive sheet] The insulating thermally conductive sheet of the present invention is a cured product of a thermally conductive silicone resin composition containing a thermosetting silicone resin and boron nitride, and is preferably obtained by molding a thermally conductive silicone resin composition containing boron nitride in a thermosetting silicone resin by a method described below.
[0016] [Thermal conductive silicone resin composition] The thermally conductive silicone resin composition is characterized by comprising (A) a thermosetting silicone resin and (B) boron nitride. The (A) thermosetting silicone resin is a thermosetting silicone resin (addition-curable organopolysiloxane composition) containing the following (A1) to (A3): (A1) Organopolysiloxane having two or more alkenyl groups bonded to silicon atoms in each molecule (A2) Organohydrogenpolysiloxane (A3) Hydrosilylation catalyst
[0017] [(A1) Organopolysiloxane having two or more alkenyl groups bonded to silicon atoms per molecule] The component (A1) is an organopolysiloxane having two or more alkenyl groups bonded to silicon atoms in one molecule, and serves as the main component of the thermally conductive silicone resin composition. Usually, the main chain portion is generally composed of a repeating diorganosiloxane unit. The molecular structure may include a branched structure or may be cyclic, but linear diorganopolysiloxanes are preferred from the viewpoint of physical properties such as the mechanical strength of the cured product. Examples of the alkenyl group include vinyl, allyl, propenyl, isopropenyl, butenyl, hexenyl, and cyclohexenyl groups, each of which usually has about 2 to 8 carbon atoms, and among these, lower alkenyl groups having 2 to 4 carbon atoms, such as vinyl and allyl groups, are preferred, with vinyl groups being particularly preferred. Note that it is necessary for two or more alkenyl groups to be present in one molecule, and in order to improve the flexibility of the resulting cured product, it is more preferred that the (A1) component has alkenyl groups bonded only to silicon atoms at both ends of the molecular chain. The group bonded to the silicon atom other than the alkenyl group is a monovalent hydrocarbon group, and among them, those having 1 to 10 carbon atoms, particularly 1 to 6 carbon atoms, are preferred. Examples of the monovalent hydrocarbon group include alkyl groups such as methyl, ethyl, propyl, isopropyl, butyl, isobutyl, tert-butyl, pentyl, neopentyl, hexyl, heptyl, octyl, nonyl, and decyl; cycloalkyl groups such as cyclopentyl, cyclohexyl, and cycloheptyl; aryl groups such as phenyl, tolyl, xylyl, and naphthyl; and aralkyl groups such as benzyl, phenylethyl, phenylpropyl, and methylbenzyl. Preferred are alkyl groups having 1 to 3 carbon atoms, such as methyl, ethyl, and propyl, and phenyl groups. In addition, the groups bonded to the silicon atom other than the alkenyl group are not limited to being all the same, and may be groups in which different types of groups are bonded to the silicon atom. The kinetic viscosity of the organopolysiloxane of component (A1) at 25°C is usually 10 to 100,000 mm 2 / s, and particularly preferably 100 to 100,000 mm 2 / s. The kinetic viscosity is in the range of 10 mm 2 / s or more, the resulting resin composition has good storage stability, and 2 If the viscosity is 1 / s or less, the extensibility of the resulting resin composition will not deteriorate. In this specification, the kinematic viscosity is a value at 25°C when using a Cannon-Fenske viscometer described in JIS Z 8803:2011. The organopolysiloxane of the component (A1) may be used either alone or in combination of two or more different types having different structures or kinematic viscosities.
[0018] [(A2) Organohydrogenpolysiloxane] The component (A2) is an organohydrogenpolysiloxane, and is characterized by being a mixture of the following components (A2-a) and (A2-b).
[0019] (A2-a) Organohydropolysiloxane represented by the following formula (a): [ka] (m is 2 or 3, n is a number from 10 to 50, and the bonding order of each siloxane unit bounded by m and n may be block or random.)
[0020] (A2-b) Organohydropolysiloxane represented by the following formula (b): [ka] (p is a number between 10 and 30.)
[0021] The organohydrogenpolysiloxane of component (A2-a) is an organohydrogenpolysiloxane that has two or three hydrogen atoms (hydrosilyl groups) directly bonded to silicon atoms in each molecule, and acts as a crosslinking agent for component (A1). That is, the hydrosilyl groups in component (A2-a) are added to the alkenyl groups in component (A1) through a hydrosilylation reaction promoted by the hydrosilylation catalyst of component (A3) described below, thereby forming a three-dimensional network structure. On the other hand, organohydrogenpolysiloxanes having hydrosilyl groups only at both ends of component (A2-b) only serve to extend the molecular chain and do not impede the free movement of the molecules, even when added to alkenyl groups in component (A1).
[0022] The molar ratio of the (A2-a) component to the (A2-b) component is (A2-a) component:(A2-b) component=1:0.2 to 1:2, more preferably 1:0.3 to 1:1.6, and even more preferably 1:0.4 to 1:0.8. If the (A2-a) component:(A2-b) component ratio is less than 1:0.2, the proportion of chain extension decreases, and the flexibility of the cured product is impaired. On the other hand, if the (A2-a) component:(A2-b) component ratio exceeds 1:2, the proportion of three-dimensional crosslinked structure decreases, making it difficult to cure the composition.
[0023] The amount of component (A2) added is an amount such that the hydrosilyl groups derived from component (A2) are 0.7 to 1.2 moles per mole of alkenyl groups derived from component (A1) (i.e., an amount such that the number of moles of hydrosilyl groups is 0.7 to 1.2 times the number of moles of alkenyl groups derived from component (A1)). If the amount of hydrosilyl groups derived from component (A2) is less than 0.7 moles per mole of alkenyl groups derived from component (A1), curing will not occur. If the amount exceeds 1.2 moles, the cured product will lose flexibility and may become brittle.
[0024] [(A3) Hydrosilylation catalyst] The hydrosilylation catalyst of component (A3) is a catalyst for promoting the addition reaction between the alkenyl group derived from component (A1) and the hydrosilyl group derived from component (A2), and examples of such catalysts include those well known as catalysts used in hydrosilylation reactions. Specific examples of such catalysts include platinum group metals such as platinum (including platinum black), rhodium, and palladium; platinum chloride, chloroplatinic acid, and chloroplatinic acid salts such as H2PtCl4·nH2O, H2PtCl6·nH2O, NaHPtCl6·nH2O, KHPtCl6·nH2O, Na2PtCl6·nH2O, K2PtCl4·nH2O, PtCl4·nH2O, PtCl2, Na2HPtCl4·nH2O (wherein n is an integer of 0 to 6, preferably 0 or 6); alcohol-modified chloroplatinic acid (see the specification of U.S. Pat. No. 3,220,972); complexes of chloroplatinic acid and olefins (see U.S. Pat. Nos. 3,159,601, 3,159,662, and 3,775,452); platinum black, palladium, or other platinum group metal supported on a support such as alumina, silica, or carbon; rhodium-olefin complexes; chlorotris(triphenylphosphine)rhodium (Wilkinson's catalyst); complexes of platinum chloride, chloroplatinic acid, or chloroplatinate salts with vinyl group-containing siloxanes, particularly vinyl group-containing cyclic siloxanes. The content of component (A3) is 100 to 3,000 ppm, preferably 100 to 2,000 ppm, calculated as the mass of platinum group metal element relative to component (A1). If the content of component (A3) is 100 ppm or more, sufficient catalytic activity is obtained, and if it is 3,000 ppm or less, the effect of promoting the addition reaction is sufficient and costs can be suppressed.
[0025] [(B) Boron nitride] The boron nitride of component (B) is a particle that is oriented in the thickness direction of the insulating heat conductive sheet (hereinafter also simply referred to as "sheet") and promotes heat conduction. From the viewpoint of heat conduction and electrical insulation in the thickness direction of the sheet, the boron nitride of component (B) is particularly preferably hexagonal boron nitride. Furthermore, its shape has a specific average particle size and aspect ratio as described below, and is preferably flat, scaly, plate-like, or flake-like.
[0026] The aspect ratio of boron nitride is 20 to 100, preferably 30 to 100, and more preferably 50 to 100. When the aspect ratio is 20 or more, the orientation important for increasing thermal conductivity is ensured, and high thermal conductivity can be imparted in the thickness direction of the sheet. Also, when the aspect ratio is 100 or less, the flexibility of the sheet can be maintained. In this specification, the aspect ratio is the major axis of a particle divided by the thickness of the particle, i.e., major axis / thickness. When a particle is spherical, the aspect ratio is 1, and as the particle becomes more flat, the aspect ratio increases. In this specification, the aspect ratio is a value obtained by measuring the major axis and thickness of a particle at a magnification of 1500 times using a scanning electron microscope and calculating the major axis / thickness.
[0027] The average particle size of boron nitride is 40 to 100 μm, more preferably 40 to 90 μm, and particularly preferably 50 to 80 μm. In order to impart flexibility to the sheet, it is necessary to efficiently form a heat conduction path in the thickness direction, and if it is less than 40 μm, the thermal conductivity is insufficient. If it exceeds 100 μm, the flexibility of the sheet is impaired. The boron nitride to be used may have a single average particle size, or multiple types having different average particle sizes may be mixed. The average particle size is the median size (the particle size at which, when a powder is divided into two at a certain particle size, the particles larger than that particle size and the particles smaller than that particle size are equal; commonly known as D50) measured by the laser diffraction / scattering method using a laser diffraction / scattering particle size distribution analyzer.
[0028] The content of boron nitride is 150 to 500 parts by mass, and preferably 200 to 400 parts by mass, per 100 parts by mass of component (A). If the content of boron nitride is less than 150 parts by mass, sufficient thermal conductivity cannot be obtained in the thickness direction of the sheet, whereas if it exceeds 500 parts by mass, the sheet becomes rigid and lacks flexibility.
[0029] In addition, insulating inorganic particles such as alumina, magnesia, aluminum hydroxide, aluminum nitride, silicon nitride, silica, etc. may be used in combination as long as the orientation of boron nitride is not hindered. By using other insulating inorganic particles in combination, the viscosity of the composition can be adjusted, which may be preferable in terms of processability.
[0030] [Other ingredients] If necessary, the thermally conductive silicone resin composition may further contain components such as a solvent, a thixotropy imparting agent, a dispersing agent, a curing agent, a curing accelerator, a retarder, a slight tackifier, a plasticizer, a flame retardant, an antioxidant, a stabilizer, and a colorant.
[0031] The thermally conductive silicone resin composition may contain a filler other than the component (B). Specific examples include silica, titanium oxide, etc. The amount of the filler to be added is not particularly limited as long as it does not impair the effects of the present invention, but is preferably 0 to 60 parts by mass, more preferably 0 to 40 parts by mass, per 100 parts by mass of the component (A).
[0032] [Method for producing thermally conductive silicone resin composition] The thermally conductive silicone resin composition can be produced by mixing (A) the thermosetting silicone resin, (B) boron nitride, and, if necessary, the other components described above, using a mixer or the like. The (A) thermosetting silicone resin may be prepared by previously mixing the (A1) component, the (A2) component consisting of (A2-a) and (A2-b), and the (A3) component using a mixer or the like, and then mixing with the (B) boron nitride or the like, or by mixing the (A1) thermosetting silicone resin and the (A2) boron nitride or the like at the same time without previously mixing them.
[0033] [Manufacturing method of insulating heat conductive sheet] The method for producing the insulating thermally conductive sheet of the present invention includes the steps of molding and curing the thermally conductive silicone resin composition, and examples thereof include the following methods.
[0034] [Method of manufacturing insulating thermal conductive sheet (1)] An example of a method for producing the insulating thermally conductive sheet of the present invention is as follows: a filling step of filling a mold with the thermally conductive silicone resin composition; a vibration step of ultrasonically vibrating the mold to degas and align the boron nitride; a heating step of obtaining a string-like semi-cured silicone composition from the thermally conductive silicone resin composition by heating; a molding step in which the string-like semi-cured silicone composition is arranged in the longitudinal direction and heated and pressurized to obtain a thermally conductive silicone molded body; a slicing step of slicing the thermally conductive silicone molded body to obtain an insulating thermally conductive sheet of a desired thickness; One example is the manufacturing method (1) that involves the steps of: This method makes it possible to obtain a flexible insulating heat conductive sheet that has excellent thermal conductivity in the thickness direction by highly orienting boron nitride. Each step of the production method (1) will be described in detail below.
[0035] Filling process (1) (Mold used in filling process) The mold used in the filling step has a width of 5.0 mm or less, a depth of width length + 1.0 mm or more, and a length of 10.0 mm or more, and has at least one groove portion whose bottom shape is not particularly limited, but examples of which include wedge-shaped, semicircular, wavy, flat, etc. Fig. 1 is a perspective view showing an example of the mold used in the filling step, and Fig. 2 is a cross-sectional view of the mold shown in Fig. 1 taken along line AA.
[0036] (Filling method) In the filling step, a specified amount of the thermally conductive silicone resin composition may be filled into the mold groove, or a large amount of the thermally conductive silicone resin composition may be filled and then the unnecessary portion may be scraped off with a squeegee or the like. Adding a solvent to the thermally conductive silicone resin composition is preferable because it reduces the viscosity of the composition and improves the filling property, and also makes it easier for the long axis direction of the boron nitride to be aligned along the long axis direction of the string-like semi-cured silicone composition when degassing and settling the boron nitride in the next vibration step.
[0037] Vibration process (1) The vibration step is performed by ultrasonically vibrating the mold filled with the thermally conductive silicone resin composition to degas and align the boron nitride. In order to obtain a string-like semi-cured silicone composition in the next heating step, the mold is ultrasonically vibrated to degas and precipitate and orient the boron nitride, thereby aligning the boron nitride in the longitudinal direction of the string-like semi-cured silicone composition. The frequency of the vibration step is preferably 28 to 120 kHz, more preferably 40 to 120 kHz. The temperature of the silicone resin composition during the vibration step is preferably 40° C. or lower so as not to accelerate the curing reaction.
[0038] Heating process (1) The heating step is a step of filling the heat conductive silicone resin composition and heating the heat conductive silicone resin composition in the mold after the vibration step to obtain a string-shaped semi-cured silicone composition that conforms to the shape of the groove of the mold. If the heat conductive silicone resin composition contains a solvent, the heating step also includes a step of volatilizing the solvent by heating. The heating temperature in the heating step is preferably 40 to 100°C, more preferably 60 to 80°C. The heating time is preferably 1 to 30 minutes, more preferably 1 to 10 minutes.
[0039] Molding process (1) (Molds used in the molding process) The mold used in the molding process is a concave mold with inner dimensions of width 10.0 mm or more, length 10.0 mm or more, and depth 10.0 mm or more, and is characterized by having a lower mold with a flat bottom shape and an upper mold whose width and length are shorter than the inner dimensions of the lower mold by 0.01 to 0.2 mm. The height of the upper mold is not particularly limited, but it is necessary to have a height that can pressurize the upper mold. Figure 3 is an exploded perspective view showing an example of a mold used in the molding process. The mold used in the molding process shown in Figure 3 has a lower mold with inner dimensions of width 33.0 mm (X axis), length 52.0 mm (Y axis), and depth 50.0 mm (Z axis), and an upper mold with width 32.9 mm (X axis), length 51.9 mm (Y axis), and height 40.0 mm (Z axis).
[0040] (Filling method) The string-like semi-cured silicone composition obtained in the heating step is filled into the lower mold as follows (i) or (ii). (i) Strings of semi-cured silicone composition are aligned so that their longitudinal directions are parallel to the X-axis direction of the mold, and then piled up and filled in the Z-axis direction. (ii) Strings of semi-cured silicone composition are aligned so that their longitudinal directions are parallel to the Y-axis direction of the mold, and then piled up and filled in the Z-axis direction. In this way, a molded body in which boron nitride is oriented can be obtained more preferably and efficiently. There is no particular limit to the number of string-shaped semi-cured silicone composition pieces arranged in the X-axis or Y-axis direction, and this can be determined as appropriate depending on the size of the lower mold, the size of the string-shaped semi-cured silicone composition, etc.; from the standpoint of productivity, however, it is preferably, for example, 2 to 5,000, and more preferably 5 to 3,000. Furthermore, the number of string-like semi-cured silicone compositions piled up in the Z-axis direction is preferably at least 2 (two layers), and more preferably from 5 to 3,000 (5 to 3,000 layers).
[0041] (Molding method) The molding step is a step in which the lower mold is pressed by the upper mold in the Z-axis direction and heated to completely cure the string-like semi-cured silicone composition, thereby obtaining a thermally conductive silicone molded body. As a method of applying pressure, it is preferable to gradually apply pressure from atmospheric pressure until the desired pressure is reached. The pressure applied to the mold is appropriately selected depending on the desired shape and hardness of the thermally conductive silicone molded article, but is preferably 0.1 to 20.0 MPa, and more preferably 0.5 to 5.0 MPa. The surface temperature of the lower die when the die is pressed is preferably from -10 to 40°C, and more preferably from 0 to 30°C. The surface temperature of the lower mold when curing the string-like semi-cured silicone composition is preferably 50 to 200° C., more preferably 100 to 150° C. The curing time is preferably 1 minute to 24 hours, more preferably 5 minutes to 1 hour.
[0042] Slicing process (1) The slicing step is a step of obtaining an insulating thermally conductive sheet of a desired thickness by slicing the thermally conductive silicone molded body obtained in the molding step. Specifically, in the molding step, When filling with method (i), the following is parallel to the YZ plane: When filling with method (ii), parallel to the XZ plane, By slicing each of the molded bodies to a desired thickness, an insulating and thermally conductive sheet in which the longitudinal direction of the boron nitride is oriented in the thickness direction of the sheet can be obtained.
[0043] [Manufacturing method of insulating thermal conductive sheet (2)] In addition, as a method for producing the insulating and thermally conductive sheet of the present invention that is different from the above-mentioned production method, a coating process in which the thermally conductive silicone resin composition is applied to a film separator using a Baker-type film applicator or the like to achieve a uniform thickness; a heating step of obtaining a sheet-shaped semi-cured silicone composition from the thermally conductive silicone resin composition by heating; a cutting step of peeling the thermally conductive silicone resin composition from the film separator and cutting it to fit the size of a mold used in a molding step; a molding step of arranging the sheet-like semi-cured silicone composition in the application direction and heating and pressing it to obtain a thermally conductive silicone molded body; a slicing step of slicing the thermally conductive silicone molded body to obtain a thermally conductive sheet of a desired thickness; One example is the manufacturing method (2) that involves the steps of: Each step of the production method (2) will be described in detail below.
[0044] Coating process (2) The coating step is a step of coating the thermally conductive silicone resin composition to a uniform thickness on a film separator from which the sheet-shaped semi-cured silicone composition can be peeled off in the next heating step, using a Baker-type film applicator or the like. This allows the long axis direction of the boron nitride to be aligned in the coating direction (parallel to the coating surface) of the sheet-shaped semi-cured silicone composition. The thermally conductive silicone resin composition to be coated on the film separator is, for example, uniformly coated to a thickness of preferably 100 to 2,000 μm, more preferably 300 to 1000 μm.
[0045] Heating process (2) The heating step is a step of obtaining a sheet-shaped semi-cured silicone composition by heating the thermally conductive silicone resin composition coated on the film separator in the coating step. If the thermally conductive silicone resin composition contains a solvent, the heating step also includes a step of volatilizing the solvent by heating. The heating temperature in the heating step is preferably 40 to 100°C, more preferably 60 to 80°C. The heating time is preferably 1 to 30 minutes, more preferably 1 to 10 minutes.
[0046] Cutting process (2) The cutting step is a step in which the sheet-like semi-cured silicone composition obtained in the heating step is peeled off from the film separator and cut to fit the size of the mold to be used in the subsequent molding step. It is preferable to set the cutting size to -0.3 to -1.0 mm in width and length compared to the inner dimensions of the mold, as this makes it easier to fill the sheet-like semi-cured silicone composition in the subsequent molding step.
[0047] Molding process (2) (Molds used in the molding process) This is the same as the molding step (1) described above.
[0048] (Filling method) The sheet-like semi-cured silicone composition obtained in the cutting step is then filled into the lower mold as follows (i) or (ii). (i) Sheet-shaped semi-cured silicone composition is aligned so that the coating flow direction is parallel to the X-axis direction of the mold, and then stacked and filled in the Z-axis direction. (ii) Sheets of semi-cured silicone composition are aligned so that the coating flow direction is parallel to the Y axis of the mold, and then stacked and filled in the Z axis direction. In this way, a molded body in which boron nitride is oriented can be obtained more preferably and efficiently. There is no particular restriction on the number of sheets of semi-cured silicone composition arranged in the X-axis or Y-axis direction, and this can be determined appropriately depending on the size of the lower mold and the size and thickness of the sheet-like semi-cured silicone composition, etc.; from the standpoint of productivity, however, it is preferably 1 to 10, and more preferably 1 to 5. Furthermore, the number of sheets of semi-cured silicone composition stacked in the Z-axis direction is preferably at least 2 sheets (two layers), and more preferably 5 to 3,000 sheets (5 to 3,000 layers).
[0049] (Molding method) The molding step is a step in which the lower mold is pressed by the upper mold in the Z-axis direction and heated to completely cure the sheet-like semi-cured silicone composition, thereby obtaining a thermally conductive silicone molded body. As a method of applying pressure, it is preferable to gradually apply pressure from atmospheric pressure until the desired pressure is reached. The pressure applied to the mold is appropriately selected depending on the desired shape and hardness of the thermally conductive silicone molded article, but is preferably 0.1 to 20.0 MPa, and more preferably 0.5 to 5.0 MPa. The surface temperature of the lower die when the die is pressed is preferably from -10 to 40°C, and more preferably from 0 to 30°C. The surface temperature of the lower mold when curing the sheet-shaped semi-cured silicone composition is preferably 50 to 200° C., more preferably 100 to 150° C. The curing time is preferably 1 minute to 24 hours, more preferably 5 minutes to 1 hour.
[0050] Slicing process (2) The slicing step is a step of obtaining an insulating thermally conductive sheet of a desired thickness by slicing the thermally conductive silicone molded body obtained in the molding step. Specifically, in the molding step, When filling with method (i), the following is parallel to the YZ plane: When filling with method (ii), parallel to the XZ plane, By slicing each of the molded bodies to a desired thickness, an insulating and thermally conductive sheet in which the longitudinal direction of the boron nitride is oriented in the thickness direction can be obtained.
[0051] [Insulating heat conductive sheet] The insulating thermally conductive sheet of the present invention preferably has the following characteristics:
[0052] [Orientation degree] The peak intensity ratio in the thickness direction detected by X-ray diffraction of the insulating thermally conductive sheet, i.e., the count sum at [2θ=41 to 43°] / the count sum at [2θ=25 to 27°], is taken as the degree of orientation, and the degree of orientation is 1 or more, preferably 2 or more.
[0053] [Hardness] From the viewpoints of ease of handling and heat dissipation, the hardness of the insulating thermally conductive sheet of the present invention is preferably an Asker C hardness of 20 to 60, more preferably 20 to 40. If the Asker C hardness is less than 20, the sheet is likely to deform during handling and may lose its orientation, whereas if the hardness exceeds 60, the contact thermal resistance between the sheet and the heating element and cooling element increases.
[0054] [Thermal Conductivity] The thermal conductivity of the insulating thermally conductive sheet in the thickness direction is preferably 16 to 30 W / mK, and more preferably 18 to 26 W / mK. The thermal conductivity is a value measured by a laser flash method (LFA 447 Nanoflash, manufactured by Netzsch) in accordance with JIS R 1611:2010.
[0055] [Breakdown voltage] The insulating thermally conductive sheet preferably has a breakdown voltage of 5 kV / mm or more, more preferably 8 kV / mm or more. The breakdown voltage is a value measured by a method in accordance with JIS C 2110.
[0056] [specific gravity] The specific gravity of the insulating thermally conductive sheet is preferably 1.2 to 2.0, and more preferably 1.4 to 1.8. The specific gravity is a value measured at 25°C by the immersion method using an automatic specific gravity measuring device (SGM-6, manufactured by Mettler) in accordance with JIS K 6249:2003. EXAMPLES
[0057] The present invention will be specifically described below using examples and comparative examples, but the present invention is not limited to these. The kinetic viscosity is the value at 25°C when using a Cannon-Fenske viscometer described in JIS Z 8803:2011, the aspect ratio is determined by SEM measurement, and the average particle size is the volume-based cumulative average particle size (median diameter) measured using a Microtrac MT3300EXII particle size analyzer manufactured by Microtrac Bell.
[0058] (Preparation of Thermally Conductive Silicone Resin Composition) The components (A) to (C) used in the following examples are shown below.
[0059] Component (A1): an alkenyl group-containing organopolysiloxane represented by the following formula: [ka] (A1-a) In the above formula, q is the kinetic viscosity at 25 ° C. of 600 mm 2 / s is the number of organopolysiloxanes (A1-b) In the above formula, q is the kinematic viscosity at 25°C of 100,000mm 2 / s is the number of organopolysiloxanes
[0060] Component (A2): Organohydrogenpolysiloxane represented by the following formula: (A2-a) [ka] (The order of the siloxane units in parentheses is arbitrary.) (A2-b) [ka]
[0061] (A3) Ingredient: 5% chloroplatinic acid solution in 2-ethylhexanol
[0062] (B) Component: Boron nitride having the following average particle size and aspect ratio: (B1) HSPD50 (average particle size 50 μm, aspect ratio 75, manufactured by Dandong Chemical Engineering Institute Co.) (B2) HSPD (average particle size 45 μm, aspect ratio 50, manufactured by Dandong Chemical Engineering Institute Co.) (B3) HSP (average particle size 40 μm, aspect ratio 30, manufactured by Dandong Chemical Engineering Institute Co.) (B4) GP (average particle size 8 μm, aspect ratio 10, manufactured by Denki Kagaku Kogyo, for comparison) (B5) PTX-60 (spherical agglomerated powder with an average particle size of 55 μm and an aspect ratio of 1, manufactured by Mommentive Co., for comparison)
[0063] (C) Component: Toluene as a diluent during kneading
[0064] The prescribed amounts of each component shown in Table 1 below were kneaded in a planetary mixer for 60 minutes to obtain a thermally conductive silicone composition.
[0065] Hereinafter, the molds used in the examples and comparative examples will be described with reference to the drawings. Figure 1 shows a perspective view of the mold used in the filling process. Figure 2 shows a cross-sectional view of the mold used in the filling process taken along line AA in Figure 1. The mold used in the filling process has multiple grooves, each 1.5 mm wide, 50.0 mm long, and 2.5 mm deep, with a semicircular bottom shape, parallel to the long axis direction of the mold. An exploded perspective view of the mold used in the molding process is shown in Figure 3. The mold used in the molding process has a lower mold with inner dimensions of 33.0 mm in width (X-axis), 52.0 mm in length (Y-axis), and 50.0 mm in depth (Z-axis), and an upper mold with dimensions of 32.9 mm in width (X-axis), 51.9 mm in length (Y-axis), and 40.0 mm in height (Z-axis).
[0066] (filling process) The thermally conductive silicone resin composition prepared above was filled so as to overflow from the groove of the mold used in the filling step, and the overflowing portion was scraped off with a squeegee.
[0067] (vibration process) The molds filled with the thermally conductive silicone resin compositions of Examples 1 to 6 and Comparative Examples 1 to 8 were vibrated for 30 minutes using a Sharp Corporation tabletop ultrasonic cleaner UT-106 under conditions of a water temperature of 25°C, a frequency of 37 kHz, and an output of 100%. The mold filled with the thermally conductive silicone resin composition of Comparative Example 9 was subjected to the subsequent heating step without the vibration step.
[0068] (Heating process) After the vibration step, the heat conductive silicone resin composition in the mold was heated in an 80°C environment for 2 minutes to obtain a string-shaped semi-cured silicone composition. In Comparative Example 9, the vibration step was omitted, and the heat conductive silicone resin composition in the mold after the filling step was heated in an 80°C environment for 2 minutes to obtain a string-shaped semi-cured silicone composition.
[0069] (molding process) The above string-shaped semi-cured silicone composition was packed into the lower part of the mold shown in Figure 3, arranged in 21 rows in the X-axis direction so that the longitudinal direction of the string-shaped semi-cured silicone composition was parallel to the Y-axis direction of the mold, and further packed into 40 layers in the Z-axis direction.Then, while applying a pressure of 1.0 MPa in the Z-axis direction with a hydraulic press in the upper part, the mixture was heated at 120°C for 30 minutes to obtain a molded product.
[0070] (Slicing process) The molded body was sliced parallel to the XZ plane with a cutter knife to obtain a sheet.
[0071] The sheets obtained in Examples 1 to 6 and Comparative Examples 1 to 9 were subjected to the following evaluations, and the results are shown in Table 1.
[0072] (hardness) A sheet sliced to a thickness of 12 mm was measured at 25° C. using an Asker C hardness tester.
[0073] (Thermal Conductivity) The sheet was sliced to a thickness of 2 mm and punched out to form a circle with a diameter of 12.7 mm. Using these as test pieces, the thermal conductivity was measured using the laser flash method (LFA 447 Nanoflash, manufactured by Netzsch) in accordance with JIS R 1611:2010.
[0074] (Breakdown voltage) The sheet was sliced to a thickness of 1 mm and immersed in oil, and the breakdown voltage was measured according to a method in accordance with JIS C 2110.
[0075] (specific gravity) The specific gravity of the sheet sliced to a thickness of 2 mm was measured at 25° C. by the underwater displacement method using an automatic specific gravity measuring device (SGM-6, manufactured by Mettler) in accordance with JIS K 6249:2003.
[0076] (degree of orientation) The sheet was sliced to a thickness of 2 mm and punched out to a circle with a diameter of 12.7 mm. These were used as test pieces and analyzed by a tabletop powder X-ray diffraction apparatus, D2 PHASER 2nd Generation, manufactured by BRUKER JAPAN. Scan range: 20-90°, Step size: 0.024°, Sample rotation: 10 rpm, Voltage: 30kV, Current: 10mA The measurement was performed under the above conditions, and the sum of the count numbers at 2θ=41 to 43° (100 plane) and 25 to 27° (002 plane) was calculated. The degree of orientation was defined by the following formula. Orientation degree = sum of counts at [2θ=41~43°] / sum of counts at [2θ=25~27°]
[0077] [Table 1]
[0078] From Examples 1 to 3 and Comparative Examples 1 and 2, it was found that a sheet with an appropriate hardness could be obtained by adjusting the molar ratio of the hydrosilyl groups in the (A2) component to the alkenyl groups in the (A1) component. On the other hand, when the ratio of the (A2) component was not appropriate, as in Comparative Examples 5 and 6, the sheet had high hardness and molding itself was difficult. On the other hand, from Comparative Examples 7 and 8, it was found that if the content of boron nitride was too high, the sheet had high hardness, and if the content was too low, the thermal conductivity was low. Looking at Examples 4 to 5 and Comparative Example 3, it was found that a suitable thermal conductivity was achieved when the average particle size of boron nitride was 40 μm or more. In addition, sheets in which the degree of orientation of boron nitride in the thickness direction of the sheet was less than 1, which was produced without a vibration step in the manufacturing process, did not form good heat conduction paths and had a lower thermal conductivity than the sheet of Example 2, which had a similar boron nitride content in the sheet. [Explanation of symbols]
[0079] 10. Molds used in the filling process 11 Groove of mold used in filling process 20 Molds used in the molding process 1. Upper die of the mold used in the molding process 2. Lower die of the mold used in the molding process
Claims
1. The following components (A) and (B): (A) A thermosetting silicone resin containing the following (A1) to (A3): 100 parts by mass (A1) Organopolysiloxane having two or more alkenyl groups bonded to silicon atoms in each molecule (A2) an organohydrogenpolysiloxane consisting of the following (A2-a) and (A2-b): an amount such that the molar ratio of the total number of hydrosilyl groups in the component (A2) to the alkenyl groups bonded to silicon atoms in the component (A1) is 0.7 to 1.2: (A2-a) Organohydropolysiloxane represented by the following formula (a): 【Chemistry 1】 (m is 2 or 3, n is a number from 10 to 50, and the bonding order of each siloxane unit bounded by m and n may be block or random.) (A2-b) Organohydropolysiloxane represented by the following formula (b): 【Chemistry 2】 (p is a number from 10 to 30) (The molar ratio of the above-mentioned (A2-a) component to the (A2-b) component is (A2-a) component:(A2-b) component=1:0.2 to 1:2.) (A3) Hydrosilylation catalyst: an amount equivalent to 100 to 3,000 ppm, calculated as platinum group metal atoms, per 100 parts by mass of component (A1) (B) Boron nitride having an average particle size of 40 to 100 μm and an aspect ratio of 20 to 100 as measured by a laser diffraction / scattering method: 150 to 500 parts by mass An insulating and thermally conductive sheet which is a cured product of a thermally conductive silicone resin composition comprising: The insulating heat conductive sheet has a thickness direction orientation degree detected by an X-ray diffraction method, in which the count sum of [2θ = 41 to 43 °] / the count sum of [2θ = 25 to 27 °] = 1 or more.
2. 2. The insulating and thermally conductive sheet according to claim 1, having an Asker C hardness of 20 to 60.
3. 3. The insulating thermally conductive sheet according to claim 1, having a thermal conductivity in the thickness direction of 16 to 30 W / mK.
4. 2. The insulating thermally conductive sheet according to claim 1, having a dielectric breakdown voltage of 5 kV / mm or more.
5. 2. The insulating and thermally conductive sheet according to claim 1, having a specific gravity of 1.2 to 2.0.
Citation Information
Patent Citations
Thermoconductive silicone composition and semiconductor device
JP2002327116A
Heat conductive sheet
JP2003145041A
Thermally conductive sheet and method of producing the same
JP2012023335A
Heat release resin sheet and device containing heat release resin sheet
JP2017036415A
Insulation heat dissipating sheet
JP2017075218A